Body mass index (BMI) as predictor of ALSFRS-R score decline in ALS patients. Issue 3 (April 2013) - Reich-Slotky, Ronit; Andrews, Jinsy; Cheng, Bin; Buchsbaum, Richard; Levy, Diane; Kaufmann, Petra; Thompson, John L. P.
Abstract Recent studies of amyotrophic lateral sclerosis (ALS) suggest that body mass index (BMI) predicts patients' survival in a curvilinear manner. We sought to determine the relationship of initial BMI to decline in the revised Amyotrophic Lateral Sclerosis Functional Rating Scale (ALSFRS-R) score over time. We used data from the high dose Coenzyme-Q10 in ALS (QALS) clinical trial, with in-person ALSFRS-R interviews at baseline and nine months (n = 150). Multiple regression analysis allowed adjustment for a range of predictors. The final analysis, adjusted for age and FVC, indicated a significant, non-linear association of BMI with the change of ALSFRS-R over time (p < 0.01). The smallest decline was at BMI of 30. Among non-obese patients (BMI < 30, n = 126), higher BMI was associated with slower ALSFRS-R decline (p = 0.03). Among obese patients (BMI ≥ 30, n = 24), higher BMI was associated, although not significantly, with faster decline (p = 0.17). In conclusion, for ALS patient with BMI less than 30, higher initial BMI predicts slower functional decline. For patients with BMI greater than 30, higher initial BMI predicts more rapid decline. These results indicate that previous, apparently contradictory results can be reconciled, and suggest that initial BMI may help predict disease progression in ALS patients.